HUBUNGAN ANTARA RIWAYAT KETURUNAN DAN FAKTOR RISIKO TERHADAP KEJADIAN ASMA: THE RELATIONSHIP BETWEEN HEREDITARY HISTORY AND RISK FACTORS FOR ASTHMA - Made Ayu Mutiara Prita Jaya; I Ketut Junitha; Ni Nyoman Wirasiti (Program Studi Biologi Universitas Udayana, 2025)
ABSTRACT Asthma is a disease caused by chronic inflammation of the respiratory tract, which causes shortness of breath and difficulty breathing. This disease arises due to genetic factors or heredity. Genetic diseases may not be inherited again in the next generation, but can recur due to several risk factors that trigger asthma. This study aims to analyze the relationship between hereditary history and risk factors on the incidence of asthma. Sampling was carried out using a purposive sampling technique, data collection was carried out by measuring the variables studied using questionnaires and interviews, and data analysis was carried out using correspondence analysis. The results of the study show that not all asthma patients have a family history of asthma, and non-genetic risk factors that cause asthma recurrence consist of age, gender, body mass index (BMI), home location, smoking habits, and environmental factors consisting of fatigue, cold weather, dust allergies, mental influences, air pollution, animal dander allergies, and food allergies. Keywords: Allergies, asthma, genetics, gender, shortness of breath, age